2008 Third International Conference on Electric Utility Deregulation and Restructuring and Power Technologies 2008
DOI: 10.1109/drpt.2008.4523611
|View full text |Cite
|
Sign up to set email alerts
|

Parallel simulation for the transient stability of power system

Abstract: Parallel time domain simulation is one of the reliable and potential methods that might realize the real-time online transient stability analysis of power system. In the paper, a new parallel calculation method, based on waveform relaxation method, is proposed for power system transient stability analysis. In the method, the entire transmission network is first divided into several subsystems by the geographical location; for each subsystem, its neighboring systems are represented as equivalent voltage sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Real-time Contingency and Transient stability with PMV [236] and other formulations with MPI [237] [238]. Faster than real-time transient stability simulation was achieved combining MPI and multi-threading techniques with network and time-domain decomposition in [239], [214] and [240]. Later algorithms were used [241].…”
Section: Developmentmentioning
confidence: 99%
“…Real-time Contingency and Transient stability with PMV [236] and other formulations with MPI [237] [238]. Faster than real-time transient stability simulation was achieved combining MPI and multi-threading techniques with network and time-domain decomposition in [239], [214] and [240]. Later algorithms were used [241].…”
Section: Developmentmentioning
confidence: 99%
“…The simulation research Literature [15], [16] performed simulations in transient voltage stability with waveform relaxation method and software MATLAB respectively, the literature [15] proposed parallel strategy has significantly higher than parallel acceleration and computational efficiency, if further combined with some effective measures to speed up, will make the simulation calculation speed to be further improved, so as to achieve the large-scale system online real-time simulation requirements. Literature [16] concluded with transient voltage stability in researching the problems, must want to consider to load the dynamic characteristic from the simulation research found in other, relaying protection action time, asynchronous motor inertia, parallel reactive power compensation devices are about system transient voltage stability impact.…”
Section: Applied Mechanics and Mechatronics Automationmentioning
confidence: 99%
“…The method has a rigorous theoretical support. In [5], independent two stages of "search+adjust" strategy are proposed based on graph theory. It reduces the partitioning calculation scale greatly, but the solution is only approximate.…”
Section: Introductionmentioning
confidence: 99%